Tumor innervation and clinical outcome in pancreatic cancer - Aysha Ferdoushi (Nature Portfolio, 2021)
Abstract Pancreatic cancer is a highly aggressive malignancy characterized by poor survival, recurrence after surgery and resistance to therapy. Nerves infiltrate the microenvironment of pancreatic cancers and contribute to tumor progression, however the clinicopathological significance of tumor innervation is unclear. In this study, the presence of nerves and their cross-sectional size were quantified by immunohistochemistry for the neuronal markers S-100, PGP9.5 and GAP-43 in a series of 99 pancreatic cancer cases versus 71 normal adjacent pancreatic tissues. A trend was observed between the presence of nerves in the tumor microenvironment of pancreatic cancer and worse overall patient survival (HR = 1.8, 95% CI 0.77–4.28, p = 0.08). The size of nerves, as measured by cross-sectional area, were significantly higher in pancreatic cancer than in the normal adjacent tissue (p = 0.002) and larger nerves were directly associated with worse patient survival (HR = 0.41, 95% CI 0.19–0.87, p = 0.04). In conclusion, this study suggests that the presence and size of nerves within the pancreatic cancer microenvironment are associated with tumor aggressiveness.